Prediction of Newborn Birth Weight Based on the Estimation at 20-24 Weeks of Gestation - Chi-Feng Su; Horng-Jyh Tsai; Ching-Yi Lin; Tsung-Ho Ying; Po-Hui Wang; Gin-Den Chen (Elsevier, 2010)
Objective: The aim of this study was to develop a mathematical equation to predict the birth weight during the second trimester at 20-24 weeks of gestation. Materials and Methods: In a university hospital, 110 healthy pregnant women were eligible for inclusion at 20-24 weeks of gestation. We recorded the maternal weight (pre-pregnancy, mid-pregnancy, and at delivery) and body mass index (BMI), newborn birth weight, time period from ultrasound examination to term delivery, and also the fetal biometrics sonographically at 20-24 weeks of gestation. Pearson's correlation was used to verify the extent of the relationship between all the above measurements and the newborn birth weight. Multiple regressions with the stepwise method were used to analyze maternal weight factors, fetal biometrical factors, and pregnancy interval. An equation for term birth weight estimation during the second trimester was determined. Results: Maternal BMI at mid-pregnancy, time interval from mid-pregnancy to term, and abdominal circumference had the highest correlation with newborn birth weight (r = 0.388, 0.341, and 0.315, respectively, p < 0.05). Using the stepwise regression analysis, an optimal formula with variance of 0.303 was derived: estimated birth weight = −700 + 49.766 × (mid-pregnancy BMI [kg/m2]) + 13.362 × (time interval from mid-pregnancy to term delivery [days]) + 68.696 × (abdominal circumference [cm]). Conclusion: We propose an accurate, simple, and easy formula to better assess the newborn birth weight at mid-pregnancy for the Asian population. Mid-pregnancy BMI was a more significant factor for birth weight estimation than other maternal weight factors in this study.